Adaptive Technology Integration under Institutional Constraints: Teacher Strategies, Student Engagement, and the TPACK Framework in an Indonesian Islamic Boarding School - Lusi Trisnawati; Hardi Humaedi Hidayat; Ulfi Wisa Belinda (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Educational technology integration in Islamic boarding schools (pesantren) presents a distinctive institutional challenge: these institutions impose restrictions on students' personal digital device use that are absent in mainstream schools, yet face the same societal pressure to develop twenty-first century digital competencies. This study examined the strategies employed by teachers to integrate educational technology, the forms of student engagement produced, and the supporting and inhibiting factors affecting implementation at MTs Idrisiyyah Putri a girls' pesantren-based Islamic secondary school in Indonesia. A qualitative single case study design was employed, with data collected from six participants (two teachers, one principal, three students) selected through purposive sampling, via in-depth interviews, non-participant observation, and document analysis. Data were analyzed following the Miles and Huberman interactive model (data reduction, data display, conclusion drawing). Findings reveal that teachers adopted institution-aligned adaptive strategies deploying school-provided computers, projectors, iPads, educational videos, digital presentations, and Quizizz within a framework governed by pesantren regulations. This approach produced measurable improvements in all three dimensions of student engagement: behavioural (active participation, attendance), emotional (enthusiasm, motivation), and cognitive (comprehension, critical questioning). Four contextual factors were identified: school-owned facility availability and institutional policy framing as enablers; device quantity limitations and uneven facility distribution as constraints. Critically, pesantren restrictions did not function as absolute barriers but as adaptive constraints that promoted teacher pedagogical creativity. Theoretically, the findings extend the TPACK framework (Mishra & Koehler, 2006) and student engagement theory (Fredricks et al., 2004) to pesantren institutional contexts, demonstrating that technology integration effectiveness is principally determined by teachers' contextual TPACK capacity rather than by facility abundance.